2004
DOI: 10.2214/ajr.183.5.1831327
|View full text |Cite
|
Sign up to set email alerts
|

MDCT Cholangiography with Volume Rendering for the Assessment of Patients with Biliary Obstruction

Abstract: MDCT cholangiography with volume rendering is a noninvasive and fast imaging technique with high sensitivity and specificity for the diagnosis of the cause of biliary tree obstruction. It is a promising diagnostic tool for the assessment of patients with bile duct obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…S W Kim, H C Shin, H C Kim et al obstructive lesions. Undoubtedly, the recently introduced MDCT cholangiography using advanced postprocessing techniques allows for a more accurate diagnosis of biliary obstruction [13][14][15][16]. Nevertheless, our results using the axial images of a MDCT showed good accuracy for the detection of biliary obstruction; the results are comparable with a previous study using both multiplanar and minimum intensity reformations [6]; however, because an aetiological diagnosis was not made in our study, an exact comparison between the two studies may be limited.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…S W Kim, H C Shin, H C Kim et al obstructive lesions. Undoubtedly, the recently introduced MDCT cholangiography using advanced postprocessing techniques allows for a more accurate diagnosis of biliary obstruction [13][14][15][16]. Nevertheless, our results using the axial images of a MDCT showed good accuracy for the detection of biliary obstruction; the results are comparable with a previous study using both multiplanar and minimum intensity reformations [6]; however, because an aetiological diagnosis was not made in our study, an exact comparison between the two studies may be limited.…”
Section: Discussionsupporting
confidence: 62%
“…They reported that the clinical diagnosis of acute cholangitis could be confirmed by demonstration of biliary obstruction using CT examination in 87% of patients. Subsequently, with advances in hardware and software technology, CT has been regarded as a reliable imaging modality with good diagnostic accuracy for biliary obstruction [5,6,[13][14][15][16]. In this study, we achieved a sensitivity of 80-84%, a specificity of 97-98% and an accuracy of 90-92% in the CT detection of biliary G, group; TS, total score.…”
Section: Discussionmentioning
confidence: 66%
“…In a large study, CTC was superior to conventional CT or US and equal to endoscopic retrograde cholangiopancreatico graphy (ERCP) for the diagnosis of HCC [102] . In another smaller study, the sensitivity and specificity of CTC for malignant biliary obstruction were both 94% [103] . One of the limitations of CTC is that optimal imaging quality depends on the secretory function of the liver [104] .…”
Section: Computed Tomography (Ct)mentioning
confidence: 89%
“…Chen et al found accuracy for intrahepatic CCC of 80% for CEUS and 67.5% for CT [46]. CT cholangiography has a diagnosis accuracy of up 94 % for intrahepatic CCC [47]. Another constant element is the retraction of the capsule (in approximately 20% of the patients) due to the fibrotic nature of the tumor [48].…”
Section: Pathologymentioning
confidence: 99%